Modeling the potential for floodwater recharge to offset groundwater depletion: a case study from the Ramganga basin, India - Chinnasamy, Pennan; Muthuwatta, Lal P.; Eriyagama, Nishadi; Pavelic, Paul; Lagudu, S. (Springer, 2018)
The Ganges basin faces considerable spatial and temporal imbalance between water demand and availability. Lack of water storage infrastructure has led to this mismatch, wherein there are limited options to store flood water during the wet season and limited groundwater and surface water resources during the dry season. In this current study, a semi-coupled hydrological modeling framework is used to test scenarios that can help bridge this imbalance. A hydrological model (SWAT), groundwater model (MODFLOW) and flood inundation model (HEC-RAS) were applied to the Ramganga basin in India (*19,000 km2) to understand the baseline hydrologic regime and to test scenarios with distributed managed aquifer recharge (MAR) interventions, which when applied to at the basin scale to co-address flooding and groundwater depletion has come to be known as Underground Taming of Floods for Irrigation. The scenarios with MAR, which used available basin runoff to recharge groundwater, yielded favorable results in flood reduction and groundwater level improvement throughout the sub-basin. Groundwater levels improved within 5 years of introducing MAR, resulting in a groundwater elevation increase of up to 7 mwhen compared to baseline conditions. The HEC-RAS model indicated that a 20% reduction in basin outflow converted a 15-year flood peak to an 8-year flood peak, a 5-year peak to 3 years and a 2-year peak to 1 year. In addition, this resulted in a 10% reduction in the inundated area in all return periods tested. Therefore, distributed MAR practices can be effective in reducing the negative impacts from larger return period floods and increasing the groundwater levels.